2004
DOI: 10.1159/000082139
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and Regulation of Proliferation in the Developing Mammalian Telencephalon

Abstract: Increasing evidence suggests that classical neurotransmitters play an important morphogenetic role during development of the mammalian central nervous system. Using in vitro and in vivo models, we have previously identified a role for the N-methyl-D-aspartate (NMDA) subclass of glutamate receptors in the proliferation of striatal progenitors. Here, we compare the roles of ionotropic glutamate receptors in the proliferation of either striatal or cortical progenitors. In culture, glutamate receptor activation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 126 publications
3
38
0
Order By: Relevance
“…However, neuronal differentiation in the olfactory bulb occurs during the second day of development (Sakata et al, 2003). This taken together with our findings of an early expression of AMPARs suggests that they play similar roles in the proliferation and migration of forebrain progenitors as described for mammals (Luk and Sadikot, 2004;Manent et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, neuronal differentiation in the olfactory bulb occurs during the second day of development (Sakata et al, 2003). This taken together with our findings of an early expression of AMPARs suggests that they play similar roles in the proliferation and migration of forebrain progenitors as described for mammals (Luk and Sadikot, 2004;Manent et al, 2006).…”
Section: Discussionsupporting
confidence: 82%
“…An appropriate level of AMPA receptor activation was shown to be crucial for cell survival of early cortical neurons (Drian et al, 2001). Furthermore, AMPA receptor (AMPAR) function was shown to be involved in developmental processes including retraction and elongation of glial processes (Ishiuchi et al, 2001), proliferation of cortical progenitors (Luk and Sadikot, 2004), and the proliferation and differentiation of retinal progenitors (Martins et al, 2006). These findings suggest that AMPAR signaling and the regulation of their expression may play an important role not only in the function, but also in the development of the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, functional GluAs are expressed in proliferative neural precursor cells in addition to mature neurons (60,61). However, prior in vitro studies have not identified which cells expressing GluAs are required for progenitor differentiation (11,12). In the present study, we demonstrated that GluAs are crucial for the development of GluA-expressing cells, as shown by the partial arrestin expression and arrested axonal extension of GluAexpressing cells in promoter-induced ci-R electroporated larvae (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…For example, mouse gluA transcripts are detectable by embryonic day 10, and in zebrafish, zygotic gluA transcripts are expressed as early as the midblastula stage (4-10). These observations, combined with in vitro results, suggest a role for GluAs in neural cell proliferation (11,12). In vertebrates, GluAs form tetramers consisting of various combinations of four subunits (GluA1-GluA4) (13)(14)(15).…”
mentioning
confidence: 82%
“…NMDA at high concentrations can be cytotoxic, depending on receptor density and subunit composition [27]. NMDA could also increase cell proliferation and/or survival, as demonstrated by several groups by in vivo and in vitro experiments [28,29]. …”
Section: Resultsmentioning
confidence: 99%